ANALISIS POTENSI MASYARAKAT PROGRAM PENGEMBANGAN KAMPUNG ORGANIK DI DESA TEGAL SARI KECAMATAN BELITANG II OKU TIMUR (JASEP, 2020)
The purpose of this study was to determine how the community's potential in receiving organic village development programs in Tegal Sari Village, Belitang II District, East OKU District and to find out how the community's response to the organic village development program in Tegal Sari Village, Belitang II District, East OKU District. This research was conducted by survey method with a sampling intensity of 12.5% so as to obtain a total sample of 24 people from a total population of 441 people. From the results of the study showed that the potential of the community in accepting the organic village development program is technically ready and able, this is evidenced by the potential that can be optimally utilized, the yard with an average area of 1,088.25 m2, organic waste with an average 1.75 kg / day and livestock waste with an average of 5.95 kg / day. Community response to the establishment of organic villages is ready / agree with an index value of 67.5%.